Geography, materialism, and the neo-vitalist turn - Gandy, Matthew; Jasper, Sandra (Dialogues in Human Geography, 2017)
In her article ‘Rethinking the subject, reimagining worlds,’ Susan M. Ruddick adds to a growing body of geographical literature that adopts a neo-vitalist approach to the understanding of nature and the human subject. In this brief article we suggest that whilst Ruddick’s argument raises many interesting points it is nonetheless hampered by a limited engagement with the historiography of scientific metaphors and the wider ethical and political tensions engendered by a contemporary recourse to vitalist ontologie